The involvement of the anticodon adjacent modified nucleoside N-(9-(BETA-D-ribofuranosyl) purine-6-ylcarbamoyl)-threonine in the biological function of E. coli tRNAile. - Miller, J P (1976)
tRNAile was isolated from E. coli Cp 79 (leu-, arg-, thr-, his-, thiamin-, RCrel) which had been grown on a sub-optimal concentration of thr and was found to contain an average of 50% less N-[9-(beta-D-ribofuranosyl)- purin-6-ylcarbamoyl]threonine, t6Ado, than tRNAile from cells grown on an optimum concentration of thr and containing a normal complement of t6Ado. The two tRNA's were identical in their ability to be aminoacylated, to accept the 3'-terminal dinucleotide, and to form an ile-tRNAile-Tu-GTP complex. In contrast, the t6Ado-deficient-tRNA was significantly less efficient in binding to ribosomes compared to the normal tRNA. This difference was seen in the binding of deacylated tRNA and in the nonenzymatic and enzymatic binding of ile-tRNA, all in response to poly AUC. The t6Ado-deficient ile-tRNA demonstrated no binding at Mg2+ concentrations less than or equal to 10 mM, while the normal ile-tRNA bound at low Mg2+ concentrations. Tetracycline had the same effect on the normal as on the t6Ado-deficient ile-tRNA binding. As a control, the binding of phe-tRNA (which does not contain t6Ado) from normal and thr-starved cells in response to poly U was identical. It was concluded that t6Ado is required for proper codon-anticodon interaction.